MENENTUKAN PERAN PAY LATER DAN MOTIVASI HEDONIK TERHADAP KEPUASAN PELANGGAN YANG DIMEDIASI OLEH PEMBELIAN IMPULSIVE - Al Afif Nurizki; Putra Dumadi, Muhammad Rezky; Robert, Muhammad Zecca; Nabila Nur Ihya Ussunah; Mardatillah, Jehan Aulia; Nabilah Asyqar; Siti Desti Sekar Sari (Student Journal of Business and Management, 2026)
This study examines the impact of pay-later adoption and hedonic shopping motivation on customer satisfaction, with impulsive buying as a mediator. Findings reveal that pay-later enhances access and flexibility but reduces satisfaction by triggering impulsive purchases, leading to financial strain and regret. Conversely, hedonic motivation shows no significant effect on satisfaction. The novelty lies in identifying a “satisfaction paradox”: pay-later offers short-term benefits yet undermines long-term well-being. E-commerce platforms and pay-later providers must manage impulsive risks to foster healthier, more sustainable shopping experiences that optimize genuine consumer satisfaction.